Designing a pocket guidebook for interview success based on an investigation on the performance of engineering students in interviews - Fauzi, Wan Jumani; Yap, Chui Yan; Nor Ashikin, Abdul Aziz (2008)
This study seeks to investigate the performance of final year university students in a mock job interview. The study involves six interviewers who are highly experienced Human Resource Managers from multinational manufacturing firms and 19 interviewees who are final year students from an engineering university. Interviewees are assessed based on the following criteria: language and communication, team working, critical thinking, technical knowledge and problem solving as well as attitude. The first day results reveal that (1) students do not really perform well as they take the session lightly (2) students unwittingly give information that puts them in a negative light and (3) students have a tough time trying to get across their meaning due to poor language proficiency. The second day interview results reveal that (1) students are better prepared as they are more motivated, (2) students still unwittingly provide negative information about themselves (3) students perform better in terms of language because they have more practice. Thus, it can be concluded that the major mistake made during an interview is that candidates are not able to successfully put themselves across in a positive light, in any one or all of the criteria assessed.